ANALISIS DISPERSI EMISI CEROBONG PEMBANGKIT LISTRIK DI PT. INDONESIA POWER BALI PGU PESANGGARAN - Sutasoma, I Wayan Gde; Nuarsa, I Wayan; Sara Wijana, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 1 (2023), 2023)
Air as an important environmental component in life that needs to be maintained and improved in quality. The presence of human activity causes the composition of clean air to undergo changes. Air pollution is caused by several factors. One of them is the industrial activities of power plants that use fossil fuels and natural gas. This research was conducted to monitor the distribution of emissions produced by power plants in PT. Indonesia Power Bali PGU uses Geographic Information System (GIS) technology and is validated using the paired t-test method. The result is that the direction of distribution of each emission parameter (SO 2 , NO 2 and Dust (TSP)) follows the wind direction according to data obtained from BMKG with a downward trend according to the distance traveled. This is because emissions are propagated by wind with dispersion variables at any given distance. The degree of validity of the modeling analysis with the results of ambient air quality measurements at each monitoring point of the SO2 and NO2 parameters is no difference between the results obtained. However, for dust parameters (TSP) there are significant differences. This is due to atmospheric conditions at the time of sampling, the location of the monitoring point surrounded by buildings, 1 sample point being on the side of the highway, and community activities around the monitoring point location. Keywords: Power Plant Emission; Air Quaity Control; Geographic Information System (GIS); Gaussian Disperssion